Efektivitas Poster Pemberian Nutrisi Anak Terhadap Pengetahuan Orangtua Tentang Pemberian Nutrisi Dalam Pencegahan Stunting Di TK Bina Anaprasa Nurul Jadid - Munir, Zainal; Rohman, Abd; Putri, Fina Zaiana; Wulandari, Inayah Riski (Jurnal Keperawatan Profesional, 2021)
The increasing number of stunting in Indonesia has crossed the WHO limit and has become a national issue that the incidence of stunting leads to unmet nutritional needs starting from the fetus to the age of toddlers, toddlers to toddlers. The purpose of the study was to find out the effectiveness of posters for giving children nutrition to parents' knowledge about nutrition in preventing stunting. This research is an intervention research by providing nutrition and stunting health education with 1 group pre-post test with pictorial media in the form of posters. The technique used is total sampling, namely all parents who have children from Bina Anaprasa Kindergarten. Data was collected by using a paired T-test approach through a pre-post test. The average result obtained is an average difference with a p value of 0.031, which means that there is an increase in knowledge of parents after being given nutrition education interventions in preventing stunting.